Crystallization study of SrSnO3:Fe - Vieira, F. T. G.; Oliveira, A. L. M.; Melo, D. S.; Lima, S. J. G.; Longo, Elson [UNESP]; Maia, A. S.; Souza, A. G.; Santos, I. M. G. (Springer, 2011)
Alkaline earth stannates have recently become important materials in ceramic technology due to its application as humidity sensor. In this work, alkaline earth stannates doped with Fe3+ were synthesized by the polymeric precursor method, with calcination at 300 A degrees C/7 h and between 400 and 1100 A degrees C/4 h. The powder precursors were characterized by TG/DTA after partial elimination of carbon. Characterization after the second calcination step was done by X-ray diffraction, infrared spectroscopy, and UV-vis spectroscopy. Results confirmed the formation of the SrSnO3:Fe with orthorhombic perovskite structure, besides SrCO3 as secondary phase. Crystallization occurred at 600 A degrees C, being much lower than the crystallization temperature of perovskites synthesized by solid state reaction. The analysis of TG curves indicated that the phase crystallization was preceded by two thermal decomposition steps. Carbonate elimination occurred at two different temperatures, around 800 A degrees C and above 1000 A degrees C.
Keywords: TG/DTA; Fe3+; Crystallization